176k views
5 votes
How to solve this? If u can ols sho step by step

How to solve this? If u can ols sho step by step-example-1

1 Answer

2 votes

for example, the line is y = ax + b (1)

we have the line go through the point ( 0 ; 3 ) so y = 3 (2)

we also have the line go through the point ( 0 ; 5 ) so x = 5 (3)

And look at the picture we also have b= 3 (4)

Put (2)(3)(4) in (1) we gonna have a= -3/5

so the line gonna be y = -3/5x + 3

P/s: if you don't understand, you can try this:

we have the line go through the point ( 0 ; 3 ) so y = 3

we also have the line go through the point ( 0 ; 5 ) so x = 5

so put it in the answer :

+) -3x -5y = 15

when x = 0 => y = -3 but y = 3 so it's wrong

+) y = -3/5x + 3

when x = 0 => y = 3

when y = 0 => x = 5 it's right :))

+) 3x + 5y = 15

when x = 0

when y = 0 => x = 5 it's right :)) but write improperly :'))

+) y = -3/5 ( x - 5 )

when x = 0 => y = 3

when y = 0 => x = 5 it's right :)) but write improperly :'))

so we choose y = -3/5x + 3

ok done. Thank to me :>

User FujiRoyale
by
5.5k points